The Le Rozel footprints: snapshots of Neandertal groups in the Late Pleistocene. A combined morphometric and experimental approach - Jérémy Duveau (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
Hominin footprints represent brief moments of life and provide access to the locomotor and biological features of the individuals who left them. Because of the particular time scale that they represent and the information they provide, they make it possible to approach the size and composition of hominin groups in a different way from the methods used with the more common archaeological artefacts and osteological assemblages. Since 2012, several hundred Neandertal footprints have been discovered at Le Rozel (Normandy, France), within 5 stratigraphic sub-units dated to about 80,000 years ago. Analyses of the ichnological assemblage discovered at Le Rozel between 2012 and 2017 have identified 257 footprints, 132 of which have been digitized in 3D. This represents the largest ichnological assemblage attributed to Neandertals to date. Morphometric analyses of the 3D models of the footprints, combined with an experimental study under substrate conditions similar to those at Le Rozel, have quantified the size and composition of the groups that left them. The footprints from the most ichnologically dense stratigraphic sub-unit were left by a small group and represent 90% of children and adolescents. These results not only enhance our understanding of the Palaeolithic occupations at Le Rozel but also provide new methods and data for assessing the size and composition of Neandertal groups.